Pharmacological Potential Of Vernonia Amygdalina With Various Bioactive Compounds: A Review - Wahyudi, Wahyudi; Alya Alfianti Balqis; Delfi Yunita Lubis; Laila Sari; Risca Muril Khairani; Syifana Nadia Raisya (Sean Institute, 2024)
Indonesia, as a megadiverse country has a wealth of tropical plants which are used in traditional medicine, including Vernonia amygdalina Del. or African leaves, which are known to have various pharmacological properties. This plant contains bioactive compounds such as flavonoids, alkaloids, and saponins, which have the potential to be used as an effective alternative herbal treatment. The aim of this literature study is to explore the pharmacological potential of Vernonia amygdalina Del. (African leaves) as a medicinal plant rich in bioactive compounds. This research method was carried out using a Systematic Literature Review (SLR). The result of researchs related to Vernonia amygdalina pharmacological potential and its bioactive compound was extracted from research article that published in Indonesia on 2018-2024. Based on research on previous studies, it was found that the pharmacological effects of African leaves (Vernonia amygdalina) include antioxidants which show moderate antioxidant activity with an IC50 value of 107,839 ppm, antibacterial containing flavonoids, tannins, saponins, and alkaloids which have antibacterial activity, antihyperlipidemia which has been proven to be effective in increases HDL levels in mice and reduces free cholesterol, especially at high doses comparable to simvastatin, anticancer which has anticancer potential with strong cytotoxic activity against WiDr cells, and anti-diabetic which can increase pancreatic cell regeneration and reduce blood glucose levels. Based on a literature review, it can be concluded that African Leaf extract (Vernonia amygdalina) contains various bioactive compounds that have potential as antioxidant, antibacterial, anti-cholesterol, anticancer, and anti-diabetic agents.